The German labor market miracle, 2003-2015: An assessment - Michael C. Burda (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
This paper reviews the dramatic and widely noted developments in the German labor market in the past decade and surveys the most plausible reasons for these changes. Alternative hypotheses are compared and contrasted. I argue that the labor market reforms associated with the Agenda 2010 - the Hartz reforms - played a role at least as great as that of increasing flexibility of wage determination and the allocation of hours across workers. Until 2010, the German economic miracle could be accounted for by an expansion of part-time work, which has since been supplanted by a sustained expansion of full-time employment. Supported by wage flexibility in this segment, part-time employment represents an important new margin of flexibility in the German labor market.
Keywords: E24; J21; 330; German labor market miracle; Hartz reforms; part-time work; wage inequality